The Influence of Leadership Development on Civil Servants Performance through Work Motivation - Herman Peudada Peudada; Sugito Efendi (University of Merdeka Malang, 2023)
The aim of the research is to find out how the performance of civil servants of the Directorate General of Agrarian Affairs is through work motivation and the impact of visionary leadership, work culture and career development. Analysis The PLS-SEM (Partial least square path modeling) approach was used in this study as part of the quantitative research methodology. Use the questionnaire as the main tool for collecting data. The research sample consisted of 103 answers from a saturated sample. Discussion of the results of the research resulted in the conclusion that visionary leadership, work culture, and career development have a direct, positive, and large effect on work motivation at the Directorate General of Agrarian Management. The direct impact of civil servants performance at the Directorate General of Agrarian Management is visionary leadership, work culture, career development, and work motivation. Through work motivation, visionary leadership, work culture, and career development have an indirect and quite large impact on civil servants.